Peran Kaderisasi Partai Politik Dalam Pengajuan Calon Legislatif Dan Kepala Daerah - Rahmat Alghazali Zainur H (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2023)
This paper discusses the importance of regeneration of political parties in preparing qualified candidates for legislative and regional heads. Inclusive representation, especially in terms of gender justice, is also the focus of this writing. The purpose of this writing is to explore an understanding of the process of regeneration of political parties, the challenges faced, and efforts that can be made to improve the quality of regeneration and ensure more inclusive representation, especially in terms of gender justice. The research method used is a literature study. This study identified that the regeneration of political parties is an important process in preparing qualified candidates for legislative and regional heads. Efforts to improve the quality of cadres and ensure more inclusive representation need to be made. Challenges faced in the regeneration of political parties include favoritism, discrimination, lack of transparency, and minimal participation of women. Some efforts that can be made to improve the quality of cadre formation and achieve inclusive representation include implementing affirmative policies, gender quotas, special education and training, as well as building networks and mentoring.